Reestructuración técnico administrativa para la empresa Coinplast S.A.S (2021)
This undergraduate work presents the proposal for the realization of an administrative technical restructuring for the company Coinplast S.A.S. located in the city of Bogotá D.C. Initially, a diagnosis was made to make an internal and external analysis of the company, identifying opportunities and threats in the city and the country with the help of the PESTAL tool, identifying strengths and weaknesses with the help of the tool of the Chamber of Commerce of Bogotá and based on the tool of the Chamber of Commerce all this information strategies were established with the help of the construction of the DOFA matrix.